Dos especies naturalizadas en el NW de Marruecos. - Talavera, Salvador; Stuessy, Tod; Berjano, Regina; Cruz, Gema; Félix, Leonardo Pessoa; García-Castaño, Juan Luis; Ortiz, Mª Ángeles; Terrab, Anass; Tremetsberger, Karin; De Vega, Clara; Salgueiro, Francisco Javier (Acta Botanica Malacitana, 2003)
Two naturalized species in NW Morocco. Palabras clave. Flora, corología, especies alóctonas, Marruecos. Key Words. Flora, chorology, exotic species, Morocco.